Enhancing student development through support services in an open distance learning institution: A case study in South Africa - Lumadi, R.I. (South African Journal of Higher Education, 2021)
This article sought to investigate the implementation of curriculum through using student support services to enhance teaching and learning among students. The participants for the study were selected from students who registered for the Postgraduate Certificate in Education in Open distance e-Learning institutions. Data was collected from 20 students who were selected, using multi-stage sampling. Data pertaining to the experiences of these students were sought, using semi-structured interviews. The findings reveal that student support services were available but were not accessed by most students. The study reveals numerous student support-related challenges including poor handling of the application and registration process, delays in delivery and receiving of study material and the absence of an effective assignment feedback administration system. The study recommends that ODeL institutions endeavour to strengthen their administrative services to be more responsive to students. Furthermore, the lecturers should be oriented to provide services to students.